2013
DOI: 10.2478/aslh-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Several Methods for Calculation of Reference Evapotranspiration

Abstract: The knowledge of the evapotranspiration of natural ecosystems and plant populations is of fundamental importance in several branches of science, research and practical uses. Nevertheless, the harmonisation of the large number of methods and user needs often causes problems. The objective of the analyses was to explore the output range and sensitivity of models of different physical approaches under local conditions. We performed descriptive statistical and sensitivity analysis of 10 commonly used estimation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
1
17
0
6
Order By: Relevance
“…Therefore, the maximum, minimum, mean, lower and upper quartile of the long term daily reference evaporation for the period are shown in Rácz et al [15] stated that methods having smallest RMSE have the lowest systematic error in predicting ET 0 . …”
Section: Reference Evaporation: Comparing the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the maximum, minimum, mean, lower and upper quartile of the long term daily reference evaporation for the period are shown in Rácz et al [15] stated that methods having smallest RMSE have the lowest systematic error in predicting ET 0 . …”
Section: Reference Evaporation: Comparing the Methodsmentioning
confidence: 99%
“…Agronomists and hydrologists have little guidance [15] [26] to choose among the many available methods to estimate reference evaporation in the Ethiopian highlands where the density of weather station is low [27] [28] and often only measure temperature and precipitation. The objective of this study is, therefore, to select the most accurate method for estimating reference evaporation for the Ethiopian highlands.…”
Section: A a Adem Et Al Journal Of Water Resource And Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between local Kc and the existent FAO values is always performed to ensure the quality of the new values (Araujo et al, 2011;Cavalcante Jr et al, 2011;Rácz et al, 2013;Filho et al, 2015;Kisi, 2016). A study developed in Texas (USA) found coefficient of Pearson of 0.87 for the new values of Kc for wheat as compared to the FAO value (Ko et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Values of KC varies over the crop growth stages and increases from a minimum value at sowing until a maximum KC reaches full canopy cover, the KC tends to decline at a point after a full cover is reached in the crop season [ALLEN et al 2006;KO et al 2009]. The comparison between local KC and the existent FAO values is always performed to ensure the quality of the new values [ARAUJO et al 2011;CAVA-LCANTE et al 2011;FILHO et al 2015;KISI 2016;RÁCZ et al 2013] Overall, estimation of crop coefficient in the regions of salt affected soils can assist to improve the agricultural management. In this respect, a field experiment was conducted for determination of water stress coefficient (Ks) and KC for wheat under different salinity in the semi-arid environment.…”
Section: Introductionmentioning
confidence: 99%